Development and validation of an mRNA-based multiplex body fluid identification workflow and a rectal mucosa marker pilot study. (September 2021) - Bamberg, Malte; Dierig, Lisa; Kulstein, Galina; Kunz, Sebastian N.; Schmidt, Max; Hadrys, Thorsten; Wiegand, Peter
Abstract: Molecular identification of body fluids and tissues is crucial in order to understand the circumstances of crimes. For that reason, molecular investigations used to identify body fluids/tissues have increasingly been examined recently. Various studies have proved that messenger RNA (mRNA) profiling is a sensitive and robust method for body fluid/tissue identification. The forensically relevant body fluids/tissues blood, semen, saliva, vaginal secretion, menstrual blood and skin have all been detected successfully by applying suitable mRNA assay. However, rectal mucosa, which can be found as evidence in sexual assault cases, has been neglected in forensic investigations. So far there is no mRNA marker to detect rectal mucosa, although anal penetration occurs in a large number of sexual assaults (23.2% of female victims and 50% of male victims). In this study, specific and sensitive mRNA markers for forensically relevant body fluids were adapted and validated in an mRNA multiplex assay for routine casework. This included the implementation of a DNA/RNA re-extraction method for automated extraction that can be integrated into casework without loss of DNA. This re-extraction method and the mRNA multiplex assay were tested using casework samples. PCR-primers were designed for the identification of rectal mucosa and the more effective marker MUC12 was integrated into an extended multiplex assay. The result of our study is a highly specific and sensitive mRNA multiplex assay plus an automated DNA/RNA re-extraction method, that can be integrated into casework and identify rectal mucosa for the first time. Highlights: Adapted and optimized mRNA multiplex assay. Development of an automated DNA/RNA re-extraction method, that is able to integrate in casework without loss of DNA. Examination of casework samples. Identification of rectal mucosa using mRNA markers for the first time.